Comparative analysis of the JRL gene family in the whole-genome of five gramineous plants - Gong, Luping; Lu, Yitong; Wang, Yujie; He, Furu; Zhu, Tao; Xue, Baoping (Frontiers in Plant Science, 2024)
The Jacalin-related lectins (JRLs) gene family play a crucial role in regulating plant development and responding to environmental stress. However, a systematic bioinformatics analysis of the JRL gene family in Gramineae plants has been lacking. In this study, we identified 101 JRL proteins from five Gramineae species and classified them into eight distinct clades. Most of the AtJRL proteins clustered in the same group and were differentiated from the Gramineae JRL proteins. The analysis of protein motifs, gene structures and protein domain revealed that the JRL genes play diverse functions in Gramineae plants. Duplication events indicated that tandem duplication significantly contributed to the expansion of the JRL family, with most JRL members underwent purifying selection. Tissue expression profile analysis showed that most OsJRL genes were highly expressed in the roots, while ZmJRL genes exhibited high expression in inflorescences. Furthermore, the expression level of OsJRL and ZmJRL genes were influenced by drought, cold, heat and salt stresses, respectively, implying that these genes play important roles in response to various abiotic stresses. RT-qPCR results demonstrated that OsJRL4 was up-regulated under PEG6000 and NaCl stresses, while OsJRL12 and OsJRL26 were down-regulated under PEG6000. These findings provide comprehensive insights into the JRL gene family in Gramineae plants and will facilitate further functional characterization of JRLs.